(untitled) (Research, Society and Development, 2025)
Objective: This study aimed to analyze correlations between environmental and hemodynamic variables (heart rate, blood pressure, oxygen saturation SatO₂, and respiratory rate FR in 20 volunteers (18–60 years old) exposed to three environments: two open (Via Light and Street) and one enclosed. Methods: PM2,5, temperature, and humidity were monitored, and variables were compared using Kruskal-Wallis tests (p ≤ 0.05), Tukey’s post hoc test, and Pearson’s correlation. PM2,5, concentrations in open areas were 208% (Via Light) and 73% (Street) higher than in the enclosed environment, exceeding the WHO daily limit by 2.8 times at Via Light. Results: Significant negative correlations between PM2,5 and SatO₂ (R = -0.53) and FR (R = -0.52) were observed at Via Light. Humidity positively correlated with SatO₂ in open environments, more strongly on the Street (R² = 0.21; p = 0.04) than at Via Light (R² = 0.16; p = 0.07). PM2,5 negatively influenced SatO₂ (R² = 0.28; p < 0.01) and FR (R² = 0.27; p < 0.01) at Via Light. Conclusion: Exposure to pollutants in high-traffic areas during public transport waiting times impairs cardiorespiratory health. However, compensatory mechanisms and short exposure duration may have mitigated exacerbated hemodynamic responses, highlighting the need for larger studies with extended observation periods to better understand acute impacts.